DAMPAK KRISIS PANGAN-ENERGI-FINANSIAL (PEF) TERHADAP KINERJA KETAHANAN PANGAN NASIONAL (Forum Penelitian Agro Ekonomi, 2016)
Food-energy-financial crisis (PEF crisis), which is discussed in this paper is the spike in world food prices in 2007/2008, the competition for the utilization of food for energy demand, triggered by the world financial crisis.  This paper aims to review the impact of the PEF crisis on Indonesia's food security. Impact of PEF crisis viewed with examining the various elements of food security in the period after 2007 compared to the previous condition. The review showed that the general crisis of PEF did not significantly affect national food security conditions, indicated by the positive direction of the rate of increase in primary production and food availability. However, PEF crisis negatively impact the diversity and quality of household food consumption and household access to food. The level of food dependence on imports for strategic food types in the proportion of the recovery. Especially for the consumption of wheat, need extra attention given the imbalance in the rate of increase in consumption by domestic capacity to produce food ingredients. Although in terms of availability could be due to be met from imports, but in the long run this will further deplete foreign exchange. It is recommended that policies that focus on strategic activities and implementation of programs related to strengthening food security can be implemented in consistency and need the support of all parties for strengthening the sustainability of national food security can be maintained.
Keywords: food-energy-financial crisis; food security; krisis pangan-energi-finansial; ketahanan pangan